Copper adparticle enabled selective electrosynthesis of n-propanol. Issue 1 (December 2018) - Li, Jun; Che, Fanglin; Pang, Yuanjie; Zou, Chengqin; Howe, Jane; Burdyny, Thomas; Edwards, Jonathan; Wang, Yuhang; Li, Fengwang; Wang, Ziyun; De Luna, Phil; Dinh, Cao-Thang; et al.
Abstract The electrochemical reduction of carbon monoxide is a promising approach for the renewable production of carbon-based fuels and chemicals. Copper shows activity toward multi-carbon products from CO reduction, with reaction selectivity favoring two-carbon products; however, efficient conversion of CO to higher carbon products such as n-propanol, a liquid fuel, has yet to be achieved. We hypothesize that copper adparticles, possessing a high density of under-coordinated atoms, could serve as preferential sites for n-propanol formation. Density functional theory calculations suggest that copper adparticles increase CO binding energy and stabilize two-carbon intermediates, facilitating coupling between adsorbed *CO and two-carbon intermediates to form three-carbon products. We form adparticle-covered catalysts in-situ by mediating catalyst growth with strong CO chemisorption. The new catalysts exhibit an n-propanol Faradaic efficiency of 23% from CO reduction at an n-propanol partial current density of 11 mA cm−2 . Upgrading wasted carbon emissions to high-value, multi-carbon products provides an economic route to reduce carbon dioxide levels, but such conversions have proven challenging. Here, authors explore copper adparticles as highly active surfaces that convert CO to n-propanol with high selectivities.